Synthesis of Heteroaromatic-Fused Cyclic β-Amino Acids by Rhodium-Catalyzed Electrophilic Amination - Manoharan, Ramasamy; Asada, Yasuko; Noda, Hidetoshi; Shibasaki, Masakatsu (Synthesis, 2024)
A series of cyclic β-amino acids fused with heteroaromatic moieties was prepared by Rh-catalyzed electrophilic amination. The transformation involves a rhodium alkyl nitrene generated from substituted isoxazolidin-5-ones upon the N–O bond cleavage. These products contain an underexplored class of cyclic structures that may have specific applications in various chemistry disciplines.
Keywords: rhodium; β-amino acids; nitrene; N-heterocycle; CH functionalization